INFLUENCE OF DISASTER KNOWLEDGE RELATIONSHIP AND ENVIRONMENTAL LEADERSHIP IN OVERCOMING FLOODS WITH FLOOD DISASTER PREPAREDNESS BEHAVIOR - Sarah Agustina Rumawak; Yossa Istiadi (Universitas Pakuan, 2021)
The objective of this study is to describe and analyze the relationship between disaster knowledge and environmental leadership in dealing with floods and with flood disaster preparedness behavior in a total of 10,688 people. The sample was taken using a multistage proportional random sampling technique, namely choosing a village that was used as the sampling area and then choosing an area that was very prone to flooding, so that the Awio Village was selected with a sample of 30 respondents. The questionnaire consists of three instruments, namely the flood preparedness behavior instrument (30 questions), the disaster knowledge instrument (26 questions) and the leadership instrument (29 questions). Rating scale with five answer choices that have the lowest value of 1 and the highest value of 5, namely for positive statements and for negative statements otherwise. The results showed the relationship between knowledge and leadership simultaneously (F=280,802,sig=0,000, p0,05). The partial relationship of disaster knowledge contributes individually and significantly to disaster preparedness behavior (ꞵ=0.097, sig=0.028, p0.05) and leadership also contributes individually and significantly to disaster preparedness behavior (ꞵ=0.954, sig=0.000, p0.05). The results showed that the level of community knowledge was still low, because they did not know about the causes of the flood disaster (60% of respondents), the level of leadership was still low, it was seen that disaster preparation planning had never been carried out (50% of respondents), and the behavioral dimension was still relatively low with the percentage behavior does not care about the preservation of nature (40% of respondents). The study recommends collective leadership so that each individual will complement each other according to their strengths, so that it will increase the effectiveness of each phase of disaster management that has been planned.